Legionella longbeachae pneumonia: A case report and literature review in Japan. Issue 5 (May 2021) - Oda, Naohiro; Taki, Takahiro; Mitani, Reo; Takata, Ichiro
Abstract: Herein, we report the case of a 74-year-old man diagnosed with Legionella pneumonia detected by Loop-Mediated Isothermal Amplification (LAMP) method, which was suspected to have been transmitted from the potting soil. Legionella longbeachae was identified in the sputum culture . The patient was intubated and maintained on mechanical ventilation. Antimicrobial therapy with azithromycin was also administered. His symptoms were resolved and he was discharged after 26 days of hospitalization. Legionella longbeachae pneumonia rarely occurs in Japan, and published literature of Legionella longbeachae pneumonia cases in Japan was reviewed. Patients with severe pneumonia exposed to potting soils, but with negative urinary antigen test results, should be examined by LAMP method.